Security without obscurity : a guide to cryptographic architectures - Stapleton, Jeffrey James (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
Information security has a major gap when cryptography is implemented. Cryptographic algorithms are well defined, key management schemes are well known, but the actual deployment is typically overlooked, ignored, or unknown. Cryptography is everywhere. Application and network architectures are typically well-documented but the cryptographic architecture is missing. This book provides a guide to discovering, documenting, and validating cryptographic architectures. Each chapter builds on the next to present information in a sequential process. This approach not only presents the material in a structured manner, it also serves as an ongoing reference guide for future use--
"A CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T&F Informa plc."
Includes bibiliographical references (pages 183-187) and index.
CSE
Keywords: Telecommunication -- Security measures; Data encryption (Computer science).; Computer network architectures; Computer science